Cross-Cultural Adaptation, Validation, and Reliability Testing of the Modified Oswestry Disability Questionnaire in Persian Population with Low Back Pain - Aslan Baradaran; Mohammad H. Ebrahimzadeh; Ali Birjandinejad; Amir Reza Kachooei (Asian Spine Journal, 2016)
Study DesignProspective study.PurposeWe aimed to validate the Persian version of the modified Oswestry disability questionnaire (MODQ) in patients with low back pain.Overview of LiteratureModified Oswestry low back pain disability questionnaire is a well-known condition-specific outcome measure that helps quantify disability in patients with lumbar syndromes.MethodsTo test the validity in a pilot study, the Persian MODQ was administered to 25 individuals with low back pain. We then enrolled 200 consecutive patients with low back pain to fill the Persian MODQ as well as the short form 36 (SF-36) questionnaire. Convergent validity of the MODQ was tested using the Spearman's correlation coefficient between the MODQ and SF-36 subscales. Intraclass correlation coefficient (ICC) and Cronbach's α coefficient were measured to test the reliability between test and retest and internal consistency of all items, respectively.ResultsICC for individual items ranged from 0.43 to 0.80 showing good reliability and reproducibility of each individual item. Cronbach's α coefficient was 0.69 showing good internal consistency across all 10 items of the Persian MODQ. Total MODQ score showed moderate to strong correlation with the eight subscales and the two domains of the SF-36. The highest correlation was between the MODQ and the physical functioning subscale of the SF-36 (r=–0.54, p<0.001) and the physical component domain of the SF-36 (r=–0.55, p<0.001) showing that MODQ is measuring what it is supposed to measure in terms of disability and physical function.ConclusionsPersian version of the MODQ is a valid and reliable tool for the assessment of the disability following low back pain.